Distal femur aneurysmal bone cyst treated with two stages of surgery in the pandemic COVID-19 by excision-skeletal traction and endoprosthesis replacement: a case report - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Rhyan Darma Saputra; Fikar Arsyad Hakim; Saddalqous (Surgical Residency Program Syiah Kuala University, 2021)
Introduction: An aneurysmal bone cyst (ABC) is benign but has a progressive nature that can cause severe problems if it occurs close to joints such as the knee. The ultimate goal of treatment is to remove the tumor, maintain limb function, and prevent a recurrence. Local therapy is still better than tumor resection. This study aims to describe a rare case about distal femur ABC treated with two stages of surgery in the pandemic COVID-19 by excision-skeletal traction and endoprosthesis replacement. Case description: A 31-year-old woman presented with a lump on the right knee. The patient has complained of limping. Open biopsy was performed, and the patient was confirmed to have ABC on the distal of her right femur. The patient had a leg length discrepancy of 8 cm. We decided to do skeletal traction first. One week after the skeletal traction, the patient undergoes endoprosthesis replacement. Conclusion: The management of wide excision of the tumor requires special postoperative attention. This is because aggressive measures can reduce the recurrence rate of tumors, but large reconstructions are also needed to maintain joint function.